Politeness Strategies Performed by Teachers: A Case of Assisting Elicitation in Children with Autism - Huma Batool, Tehmina Farrukh, Sadia Irshad (JCTE, 2023)
The current research explores politeness strategies employed by the teachers for successful elicitation of language from children with Autism Spectrum Disorder (ASD). Data of the study is collected from classroom interaction of 13 verbally autistic children having bilingual background. After building the corpus, data is transcribed and analyzed on the basis of the theoretical framework proposed by Brown and Levinson (1978). The results of the study suggest that mental ability and autistic condition of children play a determining role in the selection of politeness strategy/strategies by teachers for linguistic elicitation. The findings alsosuggest that non-verbal acts performed by the teacher aid in gettingattention from children with autism.